MANFAAT, PANDANGAN, DAN ALTERNATIF PROGRAM PERHUTANAN SOSIAL DI DUA KELOMPOK RUJUKAN, KABUPATEN PEMALANG - Dicky Rachmawan; Francisia Saveria Sika Ery Seda; Robert Siburian; Danang Kuncara Sakti (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2022)
Social forestry program expected to give space for people in forest management, improve livelihood, and conserve the environment at once to decrease poverty rate on people who live around the forest. This article aims to describe the benefit of community member which is complemented by deepening of view and alternative of social forestry program in Kelompok Tani Hutan Gunung Gajah Lestari (KTH GGL) and Lembaga Masyarakat Desa Hutan Rawa Sakti (LMDH RS). Qualitative approach in case study form is used which interview 49 informants include managements and members that accompanied by focus group discussion as data triangulation which processed by Nvivo application and Microsoft Excel. The result shows social forestry program has viewed giving benefit although it felt not optimal by the members in both groups. However, rough calculation on utilization of forest areas tends possibly to contribute around Rp.1,5-3 million rupiah/planting period. The utilization of forest areas is revival means or additional income where social-economic context is needed to be understood on identify commodity alternative that can be developed in the further time. The rest is the need for natural science approach which can answer the confusion of community to find alternatives commodity which more give revenue.